Theoretical references of the work with the map for the development of the environmental education in the career Geography (REDEL. Revista Granmense de Desarrollo Local, 2021)
The university like educational institution have the social responsibility of forming the professionals to respond in pertinent form to the environmental necessities under the demands of the new paradigm of the sustainable development. In such a sense, the political will in favor of the care of the Environment is materialized in the Constitution of the Republic, in the legislative classification and in the institutional invigoration for the systemic, systematic and rational attention of the Environment. Presently work is carried out an analysis of the philosophical, sociological, psychological and pedagogic foundations and that they support the treatment of the work with the map in the development of the environmental education. The study of this important topic has a marked social interest, because it contributes to strengthen, the environmental education of the students of the career Geography, impacting in a sustainable environmental behavior, starting from the bond of the work with the map with the environmental context and favoring an integral education and contextualized; the above-mentioned denotes the necessity to approach this problem in the formative process of the professionals of the education to explore roads and methods that contribute to assume the different lists that correspond him in diverse contexts and to face the non-alone problems of the profession, but the challenges of the current society before a more and more progressive environmental crisis.
Keywords: environment; environmental education; work with the map; process formative